2009
DOI: 10.1142/s0192415x09006680
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Emblica Officinalis (Amla) Extract Reduces Oxidative Stress in Uremic Patients

Abstract: Emblica Officinalis (also known as Amla or Indian Gooseberry), a natural, traditional and functional food in Asia, has physiological benefits such as hepato-, cyto- and radio- protection, as well as hypolipidemic effects. In addition, Amla often functions as a potent antioxidant due to the high level of ascorbic acid (ranging from 1,100 to 1,700 mg/100 g of fruit) in its fruit. The aim of this study was to determine whether supplementation with Amla extract could reduce oxidative stress in patients with uremia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
1
19
0
1
Order By: Relevance
“…Recent studies try to use antioxidants as protective remedies against CI-AKI have yielded conflicting results [34-36]. Antioxidant effect of PE was demonstrated in vitro and vivo studies by increased the concentration of antioxidant enzymes SOD and CAT and decreased MDA in lipid peroxidation [37-39]. The present study demonstrated that antioxidant effect of PE extract could decrease MDA in both plasma and renal tissues.…”
Section: Discussionmentioning
confidence: 49%
“…Recent studies try to use antioxidants as protective remedies against CI-AKI have yielded conflicting results [34-36]. Antioxidant effect of PE was demonstrated in vitro and vivo studies by increased the concentration of antioxidant enzymes SOD and CAT and decreased MDA in lipid peroxidation [37-39]. The present study demonstrated that antioxidant effect of PE extract could decrease MDA in both plasma and renal tissues.…”
Section: Discussionmentioning
confidence: 49%
“…In the last study (Santus et al, 2005), the same extract was consumed also by nine healthy controls, but a significant decrease in isoprostanes excretion was found only in smokers with baseline levels higher than controls. Finally, in the study by Chen et al (2009), a decrease of plasma isoprostanes was reported after four months of consumption of Emblica officinalis (Amla or Indian goosberry) extract.…”
Section: Intervention Studies With Galenic Preparations Containing Plmentioning
confidence: 89%
“…No effect on isoprostanes and NEAC urinary levels was described by Stewart et al (2002) after a three-week supplementation with fruit and vegetable gummy supplements in 20 children. The last study reporting NEAC measurement was published by Chen et al (2009), where an increase of plasma NEAC was found together with a reduction of plasma isoprostanes after supplementation with Amla extract.…”
Section: Intervention Studies With Galenic Preparations Containing Plmentioning
confidence: 99%
“…Earlier studies used dosages of 800 mg of EGCG=day 18 and 450 mg of AE=day for a human study. 19 We used dosages of 300 mg of EGCG and 300 mg of AE=day in this study. The plasma antioxidant=oxidative status was investigated in uremic patients with diabetes after they received 1:1 EGCG= AE for 3 months.…”
Section: Discussionmentioning
confidence: 99%